1974
DOI: 10.1177/000348947408300518
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytes of the Vestibular Labyrinth and Their Relationship to the Microvasculature

Abstract: The melanocytes of the vestibular labyrinth as seen in colored guinea pigs show a characteristic pattern of distribution in the wall of the utricle and in the ampullae, but they are not present in the wall of the saccule. They are found mainly in well-vascularized regions of apparent secretory or metabolic importance, including the "dark cell" areas. Their dendrite-like processes are often in intimate contact with the capillaries, although no pinocytotic vesicles or other indications of transfer of substances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 10 publications
4
47
1
Order By: Relevance
“…3A), spiral ligament, modiolus, osseous spiral lamina, macula, ampulla, and semicircular canals and around the endolymphatic duct and sac in all three groups. Similar results have been seen for most other pigmented mammalian species (Wolff 1931;Savin 1965;La Ferriere et al 1974;Hilding and Ginzberg 1977;Franz et al 1990;Gratton and Wright 1992). There was a significant increase of melanin pigment in the stria vascularis, spiral ligament, and maculae of the aged inner ear (data not shown).…”
Section: Histochemistrysupporting
confidence: 83%
“…3A), spiral ligament, modiolus, osseous spiral lamina, macula, ampulla, and semicircular canals and around the endolymphatic duct and sac in all three groups. Similar results have been seen for most other pigmented mammalian species (Wolff 1931;Savin 1965;La Ferriere et al 1974;Hilding and Ginzberg 1977;Franz et al 1990;Gratton and Wright 1992). There was a significant increase of melanin pigment in the stria vascularis, spiral ligament, and maculae of the aged inner ear (data not shown).…”
Section: Histochemistrysupporting
confidence: 83%
“…The distribution of melanocytes in the modiolus and vestibular partition agreed very well with that reported in other species (Wolff, 1931;Kimura, 1969;LaFerriere et al, 1974;Franz et al, 1990) and no difference was observed between the distribution of melanocytes in pigmented and albino animals. In contrast to the strial melanocytes, they showed the same character istics as skin melanocytes in both strains.…”
Section: Discussionsupporting
confidence: 89%
“…There is a close correlation b e tween the distribution of pigmented cells and dark cells and they are separated from the dark cells by a basal lamina (Kimura, 1969;LaFerriere et al, 1974).…”
Section: Introductionmentioning
confidence: 95%
“…3 There are many melanocytes in the human cochlea, particularly in the modiolus, in the osseous spiral lamina, in Reissner's membrane and in the vascular stria; melanocytes are found especially in highly vascularized areas of apparently important secretory or metabolic function. [3][4][5] Although its exact role -and that of melanin -remains unknown, it is probable that they have a vasomotor function in the inner ear. 3,4 According to Savin (1965) The inner ear contains many melanocytes, particularly in the basal area of the cochlea, which is responsible for high sound frequencies, those that are affected earlier by ototoxic drugs and intense noise exposure.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Although its exact role -and that of melanin -remains unknown, it is probable that they have a vasomotor function in the inner ear. 3,4 According to Savin (1965) The inner ear contains many melanocytes, particularly in the basal area of the cochlea, which is responsible for high sound frequencies, those that are affected earlier by ototoxic drugs and intense noise exposure. 4,6,7 Conlee et al (1995) studied the effect of gentamicin in animals and concluded that melanin could inhibit the toxicity of these drugs by binding to them; melanin would thus have a protective role for the cochlea.…”
Section: Introductionmentioning
confidence: 99%